Bibliometric analysis of tumor marker application in gastric cancer diagnosis from 2019 to 2024 - Komekbay, Zhanat; Shirazi, Reza; Yessultanova, Gulnaz; Garifollin, Alisher; Tulyayeva, Anar; Kereyeva, Nurgul; Akhmetova, Saule; Kaliev, Abdiraman (Frontiers in Medicine, 2025)
Gastric cancer remains a significant global health challenge, ranking fifth worldwide in both incidence and mortality worldwide. Early detection and accurate prognosis are crucial for effective management, yet current diagnostic methods, including tumor markers, often exhibit less sensitivity. This bibliometric analysis investigates trends and key contributions in research on tumor markers for gastric cancer diagnosis from 2019 to 2024. Using Scopus and Web of Science databases, 2,940 articles were analyzed to assess publication trends, prominent authors, institutions, and emerging research themes. Results highlight East Asia, particularly institutions like Fudan University and Nanjing Medical University, as a hub for groundbreaking research. The study identifies key tumor markers and advances in molecular diagnostics, with emphasis on personalized medicine and early detection strategies. Visualization of global collaborations reveals extensive networks driving innovation in this field. While this analysis underscores progress in gastric cancer biomarker research, it also identifies limitations, including language bias and a narrow temporal scope. Future research should prioritize novel biomarkers, integrate advanced technologies like AI, and enhance international cooperation to further improve outcomes for gastric cancer patients.